2022
DOI: 10.1126/sciadv.abn0356
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal hyperactivity–induced oxidant stress promotes in vivo α-synuclein brain spreading

Abstract: Interneuronal transfer and brain spreading of pathogenic proteins are features of neurodegenerative diseases. Pathophysiological conditions and mechanisms affecting this spreading remain poorly understood. This study investigated the relationship between neuronal activity and interneuronal transfer of α-synuclein, a Parkinson-associated protein, and elucidated mechanisms underlying this relationship. In a mouse model of α-synuclein brain spreading, hyperactivity augmented and hypoactivity attenuated protein tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 76 publications
0
35
0
Order By: Relevance
“…A separate recent study provided further evidence of oxidant stress as a mechanism promoting α-synuclein pathology in the vagal model [50]. As described above, this pathology is markedly affected by neuronal activity, with hyperactivity enhancing both hα-synuclein aggregation and spreading.…”
Section: Mechanisms Promoting α-Synuclein Pathology In the Vagal Mode...mentioning
confidence: 70%
See 4 more Smart Citations
“…A separate recent study provided further evidence of oxidant stress as a mechanism promoting α-synuclein pathology in the vagal model [50]. As described above, this pathology is markedly affected by neuronal activity, with hyperactivity enhancing both hα-synuclein aggregation and spreading.…”
Section: Mechanisms Promoting α-Synuclein Pathology In the Vagal Mode...mentioning
confidence: 70%
“…Results revealed that, in the presence of enhanced SOD2, hyperactivityinduced oxidative burden was significantly alleviated. As importantly, SOD2 transduction completely reversed the pathological effects of neuronal stimulation on α-synuclein aggregation and interneuronal transfer, providing compelling evidence of a mechanistic link between hyperactivity, oxidant stress and α-synuclein pathology [50].…”
Section: Mechanisms Promoting α-Synuclein Pathology In the Vagal Mode...mentioning
confidence: 85%
See 3 more Smart Citations